The historical importance of the port of the Levant in the era of the Ottoman Empire (1215-1337A.H/1800-1918A.D) - Alghonaimi, Mazen (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with the importance of the ports of the Levant and its development until the end of the Ottoman period, in the most important states of the country and the closest to the center. It addresses the situation harbors and experienced difficulties ranging from berthing until the transfer of goods and services that the state has worked to availability, the difficulties encountered and the efforts to secure the movement of trade. In addition, the paper deals with the effect of nature and administrative red tape in the obstruction of the work, the inability to accommodate all sizes of vessels and the intervention of foreign countries in the development of ports through the concession system operations, with an explanation shows the effect of the geographical location of the port in the trade.